Emotional justice : a roadmap for racial healing - Armah, Esther (Berrett-Koehler Publishers, Inc., 2022)
"Amid a global racial reckoning, this book offers a much-needed language for racial healing and repair, written by an international award-winning journalist, playwright, radio host, and writer. The new world that we are currently navigating post-2020 demands global racial healing. Such work involves tough conversations around race, white supremacy, and anger. Emotional Justice offers a new language for racial healing and social justice. As Esther Armah explains, dismantling the language of whiteness requires different work from different people. The book looks at key terms-Intimate Reckoning, Intimate Revolution, Resistance Negotiation, and Revolutionary Black Grace-that enable people to challenge white supremacy. Intimate Reckoning shows white women how they can examine their role in sustaining white supremacy, while Intimate Revolution teaches Black women to unlearn the language of whiteness that teaches them their sole value is labor. The book includes exchanges with prominent thinkers in this field, including Dr. Robin DiAngelo and Courtney Martin. This book will help readers practice anti-racism and racial repair, do the work of dismantling systemic inequity, and figure out how to coexist across different perspectives"--